Reliability and safety of water supply systems in terms of changes in European Union regulations - Rak, Janusz; Tchórzewska-Cieślak, Barbara; Piegdoń, Izabela; Szpak, Dawid; Żywiec, Jakub (Instal, 2022)
The paper presents the reliability indicators used in analyzes of the functioning of water supply systems. Also the risk of lack of water supply to consumers in a crisis situation was determined. The presented approach complies with the requirements of Directive (EU) 2020/2184 of the European Parliament and of the Council of 16 December 2020, which implements a risk-based approach covering the entire water supply system in terms of supply, draw water, treatment, storage and distribution of water.